The betrayal knows my name. 7 - Odagiri, Hotaru (Asuka komikkusu DX., 2017)
"Yuki, having learned the truth of his birth while visiting the Giou main house in Kyoto, returns to Tokyo in search of answers from Takashiro. Meanwhile, on the trail of the serial killer draining corpses of blood and wreaking havoc in Ueto, Kuroto and Senshirou encounter a young man in possession of a grimoire!"--